2015
DOI: 10.1002/open.201500160
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed Trifluoromethylation of Ketones and Sulfonyl Fluorides by Fluoroform under a Superbase System

Abstract: Fluoroform (HCF3, HFC-23) is a side product in the manufacture of polytetrafluoroethylene (Teflon). Despite its attractive properties, taming HCF3 for trifluoromethylation is quite problematic owing to its low acidity and the lability of the naked trifluoromethyl carbanion generated from HCF3. Herein we report the organic-superbase-catalyzed trifluoromethylation of ketones and arylsulfonyl fluorides by HCF3. The reactions were carried out by using a newly developed “superbase organocatalyst system” consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 70 publications
1
32
0
2
Order By: Relevance
“…26,[31][32][33][34] A series of aldehydes and ketones were tested for trifluoromethylation, and gave moderate to good yields of the target products 2 in most cases. 24,[35][36][37] In these studies, various carbonyl compounds were scrutinized, giving moderate to good yields of products 2, 4 or 5 in most cases. Prakash et al showed that all the trifluoromethylation reactions, performed in THF or ether instead of DMF as solvent in the presence of fluoroform as a CF3 source and KHMDS or t-BuOK as a base, afforded the desired products 2 in 0-81% yields (Scheme 2).…”
Section: Trifluoromethylation or Difluoromethylation Of Carbonyl Compmentioning
confidence: 99%
See 3 more Smart Citations
“…26,[31][32][33][34] A series of aldehydes and ketones were tested for trifluoromethylation, and gave moderate to good yields of the target products 2 in most cases. 24,[35][36][37] In these studies, various carbonyl compounds were scrutinized, giving moderate to good yields of products 2, 4 or 5 in most cases. Prakash et al showed that all the trifluoromethylation reactions, performed in THF or ether instead of DMF as solvent in the presence of fluoroform as a CF3 source and KHMDS or t-BuOK as a base, afforded the desired products 2 in 0-81% yields (Scheme 2).…”
Section: Trifluoromethylation or Difluoromethylation Of Carbonyl Compmentioning
confidence: 99%
“…35 The other two research groups, such as Shibata and Mikami, both reported that in the effect of [(Me2N)3PN]3PNCMe3 as base, fluoroform was used for difluoromethylation reaction at lower temperature (-30 o C or -40 o C) or room temperature, and produced the compounds 2 in moderate to excellent yields (Shibata: 52-92% and 64-99%, Mikami: 48-99%, respectively). 24,36,37 In addition, the carboxylic acid esters and halides 3 were also employed for trifluoromethylation by Mikami and co-workers (Scheme 3). 36 It is very interesting that when benzoyl chloride and 1.2 equiv [(Me2N)3PN]3PNCMe3 were used for this transformation, the reaction time had no effect on the yield of the product 4 (72% yield).…”
Section: Trifluoromethylation or Difluoromethylation Of Carbonyl Compmentioning
confidence: 99%
See 2 more Smart Citations
“…This transformation, and related ones, [14] have been reported with moderate success using TMSCF 3 and TBAF,a lthough owing to the inevitable presence of water in the reagent mixture,the nature of the fluoride is uncertain because TBAF samples are almost always hydrated. This transformation, and related ones, [14] have been reported with moderate success using TMSCF 3 and TBAF,a lthough owing to the inevitable presence of water in the reagent mixture,the nature of the fluoride is uncertain because TBAF samples are almost always hydrated.…”
mentioning
confidence: 99%